Quest towards establishing the technical specifications for indigenous oil palm biomass processing machinery / Mahmudin Saleh, Abdul Rahman Omar and Mohd Nor Mohd Yusoff - Saleh, Mahmudin; Omar, Abdul Rahman; Mohd Yusoff, Mohd Nor (2004)
Prompted by their abundant availability throughout Malaysia, oil palm fibres is a very much sought after material for a wide range of downstream applications, This development coupled with inefficiencies of the conventional wood processing machines has led to the need of a reliable processing machine to extract lignocellulosic fibres from the oil palm biomass, A thorough understanding of oil palm biomass physical nature with its every possible industrial processing, is therefore a necessity towards successful development of an indigenous oil palm biomass processing machine, Hence, initiating a quest towards the development of the processing machine involving field studies conducted at commercial processing plants, assessment on key implementing agencies' involvement in oil palm biomass related R&D activities and adoption of Quality Function Deployment, a technique acknowledged for integrated product design and development. A three-stage processing is found as a pre-requisite to extract oil palm fibres while moisture level, purity and length are altogether considered being the fibres' critical characteristics toward specific end uses, Further, nine of the machine characteristics have been identified being the major specifications, leaving ten others as minor. Despite several shortcomings identified by the key agencies in the processing of oil palm biomass into fibres, findings from this study is envisaged to further catalyse the development of downstream industry from optimum utilisation of oil palm fibres for value-added products manufacture.